Past Movements, Tomorrow's Anchors. On the Relational Entanglements Between Archaeological Mobilities - Aldred, Oscar (Past Mobilities, 2014)
This chapter argues that the distinctiveness of archaeology's subject compared to other disciplines, it is its focus on materiality and temporality. It is an aspect that remains fundamental to the mobilities paradigm's transcending the dichotomy between transport research and social research, putting social relations of travel and connecting different forms of transport with complex patterns of social experience conducted through communications at a-distance'. The second is a reformulation of Deleuze and Guattari's deterritorialization which argues for an adjustment away from fixed, static structures in society. The tools that Sheller and Urry use for the mobility turn' in the social sciences are being used to examine issues associated with an increasingly connected, speeded-up world, linking topics such as globalization with the possible outcomes such as the deterritorializing of states, nations, identities and belongings. The approach taken has been a multi-disciplinary one, incorporating textual, archaeological, and environmental evidence, from the collective experiences of an international team of archaeologists, historians, and natural scientists.